2018
DOI: 10.20450/mjcce.2018.1406
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Artonin E from the root bark of Artocarpus rigida, synthesis of Artonin E acetate and evaluation of anticancer activity

Abstract: Artonin E was isolated from the root bark of A. rigida. The isolated compound was then esterified using a known procedure by the addition of acetic anhydride with pyridine catalyst. The structure of the synthesized compound was carefully determined by physical and spectroscopic techniques and compared to the data in the literature. The anticancer activity test against murine leukemia cancer cells P-388 showed that the ester compound has good activity with an IC50 of 2.79 μg/mL and much better stability during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…These features of the spectrum confirm that esterification of artocarpin involves two hydroxyl groups of the A ring on C2' and 4'. This finding is in agreement with the result of esterification of artonin E with acetic anhydride, which shows that the hydroxyl groups experiencing esterification are those attached to the A ring [39].…”
Section: -1-nmr Characterizationsupporting
confidence: 91%
“…These features of the spectrum confirm that esterification of artocarpin involves two hydroxyl groups of the A ring on C2' and 4'. This finding is in agreement with the result of esterification of artonin E with acetic anhydride, which shows that the hydroxyl groups experiencing esterification are those attached to the A ring [39].…”
Section: -1-nmr Characterizationsupporting
confidence: 91%
“…34,37 Inhibition by artonin E acetate (IC50 = 2.79 µg/mL) was not as strong but was more stable than artonin E during storage. 38 Against MCF-7 breast, MDA-MB-231 breast, HepG2 liver and WRL68 liver cancer cells, inhibition by artonin E was 2.6, 13.5, 33.8 and 29.6 µg/mL. 19 A recent study reported that artonin E inhibited the growth of SKOV-3 ovarian cancer cells in 2D and 3D cultures, with IC50 values of 6 and 25 μg/mL at 72 h, respectively.…”
Section: Anti-cancer Activities Of Artonin Ementioning
confidence: 96%
“…11 Against murine P388 leukemia cells, inhibition by artonin E was very strong with IC50 value was 0.06 µg/mL. 34,37 Inhibition by artonin E acetate (IC50 = 2.79 µg/mL) was not as strong but was more stable than artonin E during storage. 38 Against MCF-7 breast, MDA-MB-231 breast, HepG2 liver and WRL68 liver cancer cells, inhibition by artonin E was 2.6, 13.5, 33.8 and 29.6 µg/mL.…”
Section: Anti-cancer Activities Of Artonin Ementioning
confidence: 99%
“…Artoindonesianin V has shown cytotoxic effects against murine leukaemia P38 cells (Hakim et al, 2006). The artonin (art) M has been reported to be present in A. altilis (Hano et al, 1990) and A. rotunda (Suhartati et al, 2008). No studies have recorded specific medicinal effects/actions against human cell lines (Bailly, 2021).…”
Section: Receptor-ligand Complexmentioning
confidence: 99%